Inclusive education in chemistry teaching: paths to meaningful learning - Isabela Sales da Silva; Paulo Henrique Almeira da Hora (Diversitas Journal, 2023)
Inclusive education is necessary to include all citizens in school and society, providing quality and dynamic education can transform and change the lives of many disabled students. It is clear that education in our country needs adjustments so that quality education reaches all students, without exclusion. Therefore, the following work is based on a bibliographical review on the training of chemistry teachers, continuing training, regarding inclusive education and also on teaching methodology, as methods and mechanisms can facilitate the understanding of programmed content and make education meaningful. . Despite the difficulties in training and applying these methodologies, it is important that teachers and the pedagogical coordination of each school environment seek alternative methods and include inclusive education as a pedagogical objective. Inclusion is the easiest way for the disabled to remain inserted in the whole of society, whether in the labor field as well as in personal life.